Precocious Preclinical Cardiovascular Sonographic Markers in Metabolically Healthy and Unhealthy Childhood Obesity - Corica, Domenico; Oreto, Lilia; Pepe, Giorgia; Calabrò, Maria Pia; Longobardo, Luca; Morabito, Letteria; Pajno, Giovanni Battista; Alibrandi, Angela; Aversa, Tommaso; Wasniewska, Malgorzata (Frontiers in Endocrinology, 2020)
Background Childhood obesity is related to a wide spectrum of cardio-vascular and metabolic comorbidities. Objectives 1) To identify precocious, preclinical, cardiovascular sonographic modifications, in a cohort of overweight (OW) and obese (OB) children and adolescents compared to lean controls; 2) to investigate the association between clinical and metabolic variables and cardiovascular sonographic parameters; 3) to evaluate their relation with two different phenotypes of obesity: metabolically healthy obesity (MHO) and metabolically unhealthy obesity (MUO). Material and methods Fifty-nine OW and OB children and adolescents (9.8±2.9 years) and twenty matched lean controls undergone anthropometric, biochemical, echocardiography assessment and sonographic evaluation of carotid artery and ascending aorta (AA). OW and OB subjects were divided in MHO and MUO, according to Camhi et al definition (J Obes 2013:984613). Results OW and OB children showed significantly higher left ventricular (LV) dimensions and mass, carotid artery intima-media thickness (CIMT), carotid stiffness (β-index, pulse wave velocity (PWV)), significantly lower mitral peak early (E) and late (A) velocities ratio (E/A-ratio) and significantly impaired global longitudinal strain (GLS) compared to controls. BMI SD and HOMA-IR were positively significantly related to LV dimensions, LA volume and epicardial adipose tissue (EAT), and negatively to E/A ratio. Waist circumference (WC) was positively correlated to LV dimensions, LA volume, CIMT, PWV, AA diameter, EAT. Furthermore, WC was strong predictor of LV dimensions, LA volume and strain, AA stiffness and diameter; BMI SD was significantly associated with EAT, LVM-index and E/A ratio; HOMA-IR and triglycerides were significant predictors of GLS. MUO patients showed higher BMI SD (p=0.02), WC (p=0.001), WHtR (p=0.001), HOMA-IR (p=0.004), triglycerides (p=0.01), SBP (p=0.001), as well as LV dimensions, EAT (p=0.03), CIMT (p=0.01), AA diameter (p=0.02), β-index (p=0.03) and PWV (p=0.002), AA stiffness (p=0.006), and significantly impaired GLS (p=0.042) compared to MHO. Conclusions Severity of overweight, abdominal obesity, insulin resistance and MUO phenotype negatively affect cardiovascular remodeling and subclinical myocardial dysfunction in OW and OB children. MUO phenotype is likely to increase the risk to develop cardio-metabolic complications since the pediatric age. Distinction between MHO e MUO phenotypes might be useful to plan a personalized follow-up approach in obese children.